Chest wall resection for non-small cell lung cancer: A case-matched study of postoperative pulmonary function and quality of life. (April 2017) - Liu, Ming; Wampfler, Jason A.; Dai, Jie; Gupta, Ruchi; Xue, Zhiqiang; Stoddard, Shawn M.; Cassivi, Stephen D.; Jiang, Gening; Yang, Ping
Highlights: A case-matched study for pulmonary function and quality of life after chest wall resection. Comparison between patients underwent pulmonary resection with and without chest wall resection. Chest wall resection do not reduce pulmonary function and quality of life dramatically. Abstract: Background: To assess the pulmonary function and quality of life (QOL) after chest wall resection for non-small cell lung cancer. Material and methods: One hundred and thirty-five patients (cases) who underwent pulmonary resection with chest wall removal were identified from January 1997 to December 2015. Propensity score matching (1:3) was applied to balance known confounders for pulmonary function and QOL between the cases and the control group who underwent pulmonary resection without chest wall invasion. Matched analyses were performed to compare perioperative mortality and morbidity, postoperative pulmonary function, overall QOL, and specific symptoms. Results: Perioperative mortality and morbidity did not differ significantly between cases and controls, but the hospital stay was longer in cases than in controls (mean, 12.8 vs 8.9 days; p < 0.001), The decline of postoperative pulmonary forced vital capacity (FVC) and the percentage of predicted FVC (FVC%) was more obvious in cases than in controls at 6 months and 2 years after surgery, but there was no obvious decline in the forced expiratory volume in one second (FEV1), the percentage of predicted FEV1 (FEV1%), the diffusion capacity of the lung for carbon monoxide (DLCO) and the percentage of predicted DLCO (DLCO%) in cases compared with controls. No significant difference was observed between the two groups in scores for overall QOL, pain, fatigue, cough, dyspnea, appetite, hemoptysis, lung cancer symptoms, and normal activities. Conclusions: When chest wall resection is inevitable, it does not worse the QOL and pulmonary function of patients who underwent pulmonary resection with chest wall removal obviously compared with patients underwent pulmonary resection without chest wall invasion.